Cinema Verite kiedy rzeczywistość staje się rozrywką zmienia się wszystko - Lane, Diane 1965-; Gandolfini, James 1961-2013 (Warner Home Video, 2012)
"A behind-the-scenes look at the making of the first American family to be the subjects of a reality TV show"--Www.imdb.com
Polnische DVD-Ausgabe
Widescreen version
Special features included
Orig.: USA, 2011
Keywords: Fernsehfilm; Americain; Cinema; Etats-Unis; Film; Loud family / Fiction; Families / Fiction; Reality television programs / Fiction; Longs métrages / États-Unis / 20e siècle; Realidad / Teatro; Loud family; Families; Reality television programs; Television programs / United States; Fiction; Feature films; DVD-Video